Normative Values for Thumb Length in Central Indian Adult Population - Agarwal, Pawan; Thatte, M. R.; Saraf, Mansi; Bobba, Rajesh; Sharma, Dhananjaya; Dhakar, Jagmoah Singh (Indian Journal of Plastic Surgery, 2024)
Introduction This article aims to establish the relative thumb length in comparison to the index finger in central Indian adults.Materials and Methods Five hundred normal adult hands (1,000 thumbs), 316 men and 184 women, mean age 30 years, were included in the study. The relative length of the thumb was measured using the length of the proximal phalanx of the index finger (thumb–proximal phalanx index) and the distance between the proximal digital crease and proximal interphalangeal crease of the index finger (thumb–digital crease index).Results The tip of a normal adducted thumb extends to 69% of the length of the proximal phalanx of the index finger and 38% of the distance between the two proximal creases of the index finger. The tip of a normal adducted thumb extends to 68% for male and 69% for female of the length of the proximal phalanx of the index finger. For the dominant hand the tip of a normal adducted thumb extends to 68%, while for nondominant hand it reaches 71% of the length of the proximal phalanx of the index finger. The difference between the laterality, gender, and hand dominance was not statistically significant.Conclusion The tip of a normal adducted thumb extends to 69% of the length of the proximal phalanx of the index finger and 38% of the distance between the two proximal creases of the index finger. Relative normal thumb length is independent of gender, laterality, or hand dominance.
Keywords: normative data; thumb length; central Indian adult; anthropometry